Building capitalism the transformation of the former Soviet bloc - Åslund, Anders 1952- (Cambridge University Press, 2002)
A most comprehensive empirical analysis of the economic transformation of the former Soviet bloc during the first decade after communism. It debunks many myths, seeing transition as a struggle between radical reformers and those thriving on rent seeking. People have gained from fast and comprehensive reforms, but several countries have gotten stuck in corruption. Economic decline and social hazards have been greatly exaggerated, since people have forgotten how awful communism was. Swift liberalization of prices and foreign trade, as well as rapid and profound fiscal adjustment, have been vital for growth, institutional reforms, legality and greater equity. Privatization has been beneficial, and its effects will grow over time. The main problem has been the continuation of unregulated and ubiquitous state apparatuses living on corruption, while no country has suffered from too radical reforms. Where malpractices of the elite can be checked, market reforms and democracy have proceeded together